PENINGKATAN KREATIVITAS PADA ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS TIK DI TK TUNAS MEKAR KECAMATAN SUKASADA KABUPATEN BULELENG - I Made Hartawan (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2020)
The learning method currently being developed is the ICT-based learning method. This happens because it is in line with the development of ICT and demands in the world of education for learning to be more advanced, more efficient and effective. So that learning objectives can be achieved properly. This study aims to determine whether ICT-based learning can increase the creativity of early childhood.This research was conducted at TK Tunas Mekar, Sukasada District, Buleleng Regency. This research is a classroom action research and consists of two cycles and each cycle consists of 4 steps, namely Planning (Planning), Action (Action), Observation (Observation), Reflection (Reflection). In this research area determination technique using purposive sampling area. Determination of respondents with Research Population. Data collection was carried out by observation and documentation. Data analysis in this classroom action research used the percentage of learning completeness formula.The results of this study indicate an increase in children's creativity and ICT-based learning. Evidently, the results of the data before using ICT-based learning were only 46.6% of students who had good creativity abilities then increased to 79.9% after using ICT-based learning. In this cycle, the child's creativity has increased and meets the 75% set target.